Is corporate governance and intellectual capital disclosure related A sri lankan case - Pratheepkanth, P. (University of Jaffna, 2018)
This study investigates the association between corporate governance and intellectual capital (IC) disclosure, controlling for firm age and leverage, for a sample of 150 Sri Lankan listed firms. The independent variables comprise various forms of corporate governance attributes: board size, board independent, board meetings and CEO role duality. IC disclosure is measured by a disclosure index. Empirical analysis is conducted using correlation and linear multiple regression analysis. Findings from the empirical analysis indicate that associations between the corporate governance and IC disclosure are generally mixed. There is still no established and generally accepted Sri Lankan framework for IC disclosure, which could be a reason for inconsistency. Results of this study provide useful information for the accounting profession, the regulators and corporations on the effective exercise of corporate governance.
Keywords: Corporate governance; Intellectual capital; Intellectual capital disclosure